Mervyn Francis Lang, Spanish word formation: Productive derivational morphology in the modern lexis. Routledge, London-New York, 1990; 270 pp. - María Eugenia Vázquez Laslop (Nueva Revista de Filología Hispánica, 1994)
Se reseñó el libro: Spanish word formation: Productive derivational morphology in the modern lexis.